Small business lending Tom the baker - Nettleton, Gavin (London : The Chartered Institute of Bankers, 1993)
This video consists of two programmes, the baker wishes to borrow some money to finance a bakery unit he has been invited to operate within a new supermarket.
Copy available in DVD format
Writer, Fred Couldery
Keywords: Small business -- Finance